A Code generator tool for the gamma design patterns / Novia Indriaty Admodisastro - Novia Indriaty, Admodisastro (2003)
Software reuse has been recognized as an attractive idea with an obvious payoff to achieve software that is faster, better and cheaper. One important component to be highlighted in designing reusable object-oriented software is design patterns. Design patterns describe a commonly recurring structure of communicating components that solve a general design problem in a particular context. An important property of design patterns is that they are independent of a particular application domain and programming paradigm. As a result, design patterns facilitate reuse of software architecture, even when other forms of reuse are infeasible. Despite the fact that design patterns have tangible benefits, it was found difficult to put into practice. Since design pattern only describes a solution to particular design problem, it does not lead to direct code reuse. Some developers have found it difficult to make a leap from the pattern description into a particular implementation. This complexity can overcome by using code generator tool that assist the developers to transform a design pattern into code automatically. There are a few existing tools in the market however most of them have limitations. Therefore, this thesis describes an attempt to automate the design patterns implementation into its concrete form and utilizing the WWW as its communication infrastructure. y-CGT is introduces to implement the main features of the existing tools and tackles some of their shortcomings. The tool has been evaluated and the results were reported to be comparable and competitive to other pattern code generator tools.